Elements of a Prophetic Voice of Dissent and Engagement (American Journal of Islam and Society, 2017)
In your hands is another thematic issue of AJISS, one that consists of two maincontributions that address the Islamic tradition’s prohibition of the homosexualact. Jonathan A. C. Brown’s essay analyzes the authenticity of pertinent hadithtraditions, whereas Mobeen Vaid’s essay explores the Qur’anic perspective.Both articles had their origin in presentations by a number of scholars at a colloquiumheld at the International Institute of Islamic Thought (IIIT) in Herndon,VA, on November 1-2, 2015. Although an earlier version of Vaid’s essay isavailable online, its original intent and thematic complementarity with Brown’sessay on hadith merit its inclusion here. Together, they make crucial contributionsto the scholarship that has reopened the question of how the Islamic scripturaland jurisprudential traditions view this particular sexual practice. In thesame workshop, I presented my reflections on the stakes of the rise of new prohomosexual(or at least neutral) laws and cultural formations for Muslim scholarshipas well as politics, which I share in a modified form in this editorialessay. In keeping with this issue’s theme of sexual ethics, we also include DavidFinn’s critical and extensive evaluation of Aysha Hidayatullah’s important FeministEdges of the Qur’an (New York: Oxford University Press, 2014) ...